Performance enhancement of cellular topologies employing dynamic cell sectoring and base station antenna beam steering using time division multiple access - Mahamod Ismail,; T.L.Doumi,; J.G.Gardiner, (1999)
This paper discusses the performance of cellular radio topologies employing dynamic cell sectoring and beam steering. Interference analysis and a teletraffic simulation study based on a TDMA cellular system employing dynamic cell sectoring and base station antenna beam steering technique has been carried out. Results in term of calls dropped, handovers per call, channel utilisation and mean value of C/I at the mobiles are compared with those obtained when omni-directional and uni-directional antenna patterns are used in base stations. Simulation results have shown that dynamic cell sectoring system improved teletraffic performances over omni-system but not over sectorisation in some cases